Girls Are So Complicated! Re-Imagining Addiction Support in Context - Newbury, Janet; Hoskins, Marie L. (Canadian Journal of Counselling and Psychotherapy, 2009)
Addiction research traditionally focuses on changing the behaviours of addicted individuals, often by locating deficits within them. This study, with 5 adolescent girls who use methamphetamines, demonstrates how photograph elicitation is used as an entry point into rich dialogue. In engaging with the photographs, narratives emerge from which researchers, teachers, practitioners, and adolescent girls can learn. This contextualized approach not only highlights the potential of a strength-based perspective, but also disperses the onus for change among helping professionals and the community at large, rather than placing responsibility for change on individuals struggling with addiction.